Pengaruh penerapan akuntansi sektor publik dan kualitas laporan keuangan terhadap akuntabilitas kinerja instansi pemerintah (studi pada Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kabupaten Kupang) - Christian Timotius Peilouw; Dwi Dayanti Oktavia; Agusta Amanda Wulandari; Chyntia Febriliany Latuan (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
This study aims to find empirical evidence of the effect of the application of public sector accounting and the quality of financial reports on the accountability performance of government agencies. This study uses three variables, namely the application of public sector accounting (X1), quality of financial reports (X2), and accountability of government agency performance (Y). This study was a quantitative study using primary data obtained through a questionnaire. The population of 54 employees of the Regional Financial and Asset Management Agency of Kupang Regency. The sample was taken 35 people using purposive sampling as the sampling technique. The data analysis method used was data quality test consisting of validity test and reliability test; and classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The hypothesis testing technique uses multiple linear regression analysis, coefficient of determination, t-test and F test. The data were processed by using the Statistical Product And Service Solution (SPSS) version 26 program. The results of this study indicated that partially the application of public sector accounting affects the accountability performance of government agencies, and partially the quality of financial reports affects the performance accountability of government agencies. Meanwhile, the simultaneous application of public sector accounting and the quality of financial reports had a significant effect on the performance accountability of government agencies